nutrition-human-health 2018
DOI: 10.35841/nutrition-human-health.2.1.13-17
|View full text |Cite
|
Sign up to set email alerts
|

College students eating habits and knowledge of nutritional requirements

Abstract: Method: This was a quantitative, cross-sectional study, with a descriptive design.Results: The students are knowledgeable that consuming fast food, soda, and processed food are unhealthy and they contain additives. They indicated strong agreement to keep themselves hydrated and choosing food because of taste preference. Even though majority admitted eating fresh fruits, a significant number consume processed food such as chips, cookies, and cereal based on convenience. Smartphone resources, vending machine use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
3
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(126 citation statements)
references
References 7 publications
8
80
3
12
Order By: Relevance
“…Previous research on generational cohorts and organic food purchasing behaviour reveals that as regards the Gen Z cohort, the results of this study are aligned with previous studies [11]. Kamenidou et al [11] found that Gen Z university students are not following an SFC behaviour, maybe due to convenience, taste, time, price, or accessibility to junk food [123,124]. As regards Gen Y (or the so-called millennials), which is the most explored generational cohort regarding OFB, previous studies demonstrate that they have keenly adopted green food [125], are willing to pay more for organic food [113], and, overall, they are more responsible consumers [126].…”
Section: Generational Cohort's Organic Purchasing Behavioursupporting
confidence: 89%
“…Previous research on generational cohorts and organic food purchasing behaviour reveals that as regards the Gen Z cohort, the results of this study are aligned with previous studies [11]. Kamenidou et al [11] found that Gen Z university students are not following an SFC behaviour, maybe due to convenience, taste, time, price, or accessibility to junk food [123,124]. As regards Gen Y (or the so-called millennials), which is the most explored generational cohort regarding OFB, previous studies demonstrate that they have keenly adopted green food [125], are willing to pay more for organic food [113], and, overall, they are more responsible consumers [126].…”
Section: Generational Cohort's Organic Purchasing Behavioursupporting
confidence: 89%
“…These results were coordinated with the results of similar studies (Genena and Salama, 2017) which presented that more than two thirds of students (72.4%) reported the intake of soft drinks . On the other hand these findings were different with (Abraham et al, 2018) which showed that a vast majority of participants (81.8%) reported that they either rarely or never drink soda. Daily consumption of snacks away from regular meals was more common among females than males (25.5% vs. 36.25% respectively) with a statistically significant difference among males and females (p=.016).…”
Section: Dietary Practicescontrasting
confidence: 70%
“…low intakes of fruit and vegetables, and breakfast/meal skipping) among university students is associated with higher levels of stress (Lee et al, 2016) and lower academic achievement (Burrows et al, 2017), motivation to improve lifestyles (de Vos et al, 2015), and the ability to empathize with others (Brehm et al, 2016). Although university students typically demonstrate an awareness of the negative impact of unhealthy food intake, convenience and taste are often higher priorities that drive their consumption behavior (Abraham, Noriega, & Shin, 2018). Academic stress combined with time and budget restrictions contribute to students' adoption of unhealthy eating patterns, thus the sacrifice of healthy food choices for convenience and "comfort foods" high in sugar, fat, and salt (Unusan, 2006;Vadeboncoeur et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%